Récréations mathématiques (1624): a study on its authorship, sources and influence - Heeffer, Albrecht (Gibecière, 2006)
In 1624 a small octavo was published in the French university town Pont-à-Mousson. It was the first time a reference was made to recreational mathematics in the title of a book. This work is pivotal in the history of science and mathematics. It brings together two sixteenth-century traditions, mercantile arithmetic and natural magic, and creates two new ones: recreational mathematics and popular science. The booklet did not abound in new ideas. Several of the recreational problems treated, can be traced back to Babylonian, Greek and Hindu sources and the infatuation with mechanical contrivances dates from Hero of Alexandria. But the fact that the book stands on the crossroad of traditions, its popularity with the natural philosophers of the seventeenth century and its complex history makes it a grateful subject for study. Some of the complexities about the numerous editions and confusing claims about its authorship will be clarified. The authors direct sources will be exposed. The arithmetical and combinatorial problems were copied from Bachet, problems on practical geometry from Jean Errard. Salomon de Caus was the source of inspiration for problems on perspective, mechanical devices and fountains. Several problems were recipies by Alexis of Piemont from the classic book by Ruscelli. The book was influencial on early seventeenth-century natural philosophers such as Descartes, Mersenne and Leibniz.